Intercolony Comparisons of Gut Microbiome Composition From Lab Reared Eastern Subterranean Termites (Blattodea: Rhinotermitidae). Issue 2 (5th April 2022) - Sapkota, R; Scharf, M E
Abstract: Termites are social insects living in colonies composed of worker, soldier, and reproductive castes. Termite hindguts are inhabited by all three domains of life- Eukarya (protists), Bacteria, and Archaea. These gut microorganisms are horizontally and vertically transferred by nestmates and reproductives, respectively. Prior evidence suggests that every colony potentially has a different gut microbiome that was transferred vertically and horizontally over time. However, we do not know if different colonies reared in the laboratory on the same diet will ultimately demonstrate similar microbial composition and structure. Therefore, we looked at gut bacteria in Eastern subterranean termite ( Reticulitermes flavipes ) colonies that were reared in the laboratory with identical diets and rearing conditions. Based on16S rRNA gene sequencing, the observed features, and Shannon's diversity were significantly different between the colonies while differences in Pielou evenness and Faith phylogenetic diversity were not statistically significant. In addition, the microbial community structures were significantly different between colonies. Based on ANCOM (Analysis of Composition of Microbiomes), the taxa Elizabethkingia (Bacteroidetes: Flavobacteriales) and Chryseobacterium (Bacteroidetes: Flavobacteriales) were differentially abundant between the colonies. These results suggest that providing the exact same diet and rearing environment for >2 yr cannot result in identical gut microbiomes between termite colonies.